Self-Care Practices Regarding Eating Habits, Knowledge of Diet and Exercise for Type II Diabetic Patients - Muhaisen, Ali Sakran; Yasir, Amean A (South Eastern European Journal of Public Health, 2024)
Background: Diabetes is an incurable condition. Adopting lifestyle modifications, including dietary adjustments and regular physical activity, plays a crucial role in effectively managing type-2 diabetes (T2DM) and preventing its potential long-term consequences. The aim of this article is to assess sociodemographic characteristics and self-care practices with eating habits patterns among T2DM.. Materials and Methods: The study chose a cross-sectional design, and the non-probability (purposive) method was used to identify participants. The total sample consisted of 150 participants who suffer from type 2 diabetes and who have patient records and files within the Diabetes Center at Marjan Medical City from June 20th, 2023, to November 10th, 2023. Results: The study findings indicated that the study showed good knowledge at Mean± SD= 2.35±0.0.46. , according to their levels of education the significance at (p<0.024 ).. Results: The study results indicate that the patients’ adherence increased as the education levels increased and vice versa. while the study showed partial adherence to diet and exercises at Mean± SD= 1.55±0.17 as well the study also found a highly significant association between the self-care practice for patients regarding the diet and exercise and some sociodemographic variables such as education levels, at a statistically significant level (p < 0.006). Conclusion: According to the results, the study concluded There was partial adherence to diet and exercise among patients with type II diabetes. However, factors such as the educational status of participants were found to influence the chance to self-care practice recommendations.